Manipulador paralelo RUS com controle de posição PID - Silva, Paulo Cesar Martins da (2018)
This work presents the development of a robotic platform with six degrees of freedom controlled via smartphone. Its objective is to offer a tool for practical activities in the area of mechatronics complementary to the theory presented in the classroom. The device consists of a parallel robot operated by six servomotors controlled by an Arduino board and the interface developed for smartphones with Android operational system that allows any student with this system to interact with the platform via Bluetooth. The execution of the project required the multidisciplinary integration of knowledge in robotics, electronics, PCB design, servo drives, programming of microcontrollers, among others. Note that this characteristic is fundamental in mechatronics. Experience has shown that the union between theory and practice can be a differential in the learning process. All subjects studied during the course have put into practice and tested, allowing better understanding and assimilation of knowledge.